Measurements of motor functional outcomes in facial transplantation: A systematic review. Issue 9 (September 2022) - Boczar, Daniel; Colon, Ricardo Rodriguez; Berman, Zoe P.; Diep, Gustave K.; Chaya, Bachar F.; Trilles, Jorge; Gelb, Bruce E.; Ceradini, Daniel J.; Rodriguez, Eduardo D.
Abstract: Although the ethical and technical feasibility of face transplant (FT) has been established, current literature lacks consensus on functional outcomes monitoring for recipients. This systematic review aims to appraise and summarize the current literature on tools used to assess motor functional outcomes in FT. This study complied with the guidelines outlined in the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA). On September 15, 2020, two reviewers conducted independent electronic searches using medical literature databases, without language or time frame limitations. Eligibility criteria included studies reporting on the evaluation of motor functional outcomes in face transplant recipients. Of 451 papers found in the literature, 12 fulfilled the study inclusion criteria. The reported tools included clinical scales/examinations, electromyography, optical movement tracking devices, muscle volumetric measurement using magnetic resonance imaging, and software-based video and photo analyses. The frequency of data collection varied from every three months to every year. Publications reporting on motor functional outcomes tracking tools vary broadly and demonstrate a lack of consensus. Although quantitative measurements are desirable, adapted clinical scales are still the current standard of care.